The era of uncertainty global investment strategies for inflation, deflation, and the middle ground - Trahan, Francois, 1969-; Krantz, Katherine, 1972-; ProQuest (Firm) (Hoboken, N.J. : Wiley, 2011)
"Macroeconomic investment strategies for an era of economic uncertaintyWith macro forces governing the post-credit crisis world, and most likely to remain dominant for some time to come, the power of the business cycle is once again in the spotlight. In this type of environment, stock picking will have far less impact on portfolio returns than getting the "big picture" right. And using the last twenty years as a playbook will prove costly to investors.The Era of Uncertainty provides a new way of thinking about investing in a dynamic, macro-driven world. In it, Fran?ois Trahan discusses the importance of macroeconomic evaluation in an unstable global economy, and goes on to cover three possible future scenarios: severe inflation, severe deflation, or a kind of muddling through. With each scenario he discusses the likely?causes and consequences as well as the best strategies for profitable investment. Draws on the experiences of prior credit-driven deleveraging cycles to develop a dynamic framework for investing in an era of economic uncertainty Contains insights on the future of the financial industry Provides fascinating anecdotes from Trahan's time at Bear Stearns prior to its collapse and sale If you intend on succeeding in today's economic environment you can't follow yesterday's investment strategies. The Era of Uncertainty reveals what it will take to make it in such a different market and how you can incorporate new strategies into your everyday investment endeavors"--
pt. 1. Why "macro matters" -- pt. 2. The roots of the new era of uncertainty : the credit crisis -- pt. 3. Current policies are leading us down an unsustainable path -- pt. 4. Investing for an uncertain future -- pt. 5. Unintended consequences and creative solutions.
Includes index.
Electronic reproduction. Ann Arbor, MI : ProQuest, 2015. Available via World Wide Web. Access may be limited to ProQuest affiliated libraries.
Keywords: Investment analysis; Macroeconomics; Uncertainty; Business cycles; Electronic books